Dynamical Core Model Intercomparison Project (DCMIP) tracer transport test results for CAM‐SE. (26th April 2016) - Hall, David M.; Ullrich, Paul A.; Reed, Kevin A.; Jablonowski, Christiane; Nair, Ramachandran D.; Tufo, Henry M.
Abstract : The Dynamical Core Model Intercomparison Project (DCMIP) provides a set of tests and procedures designed to facilitate development and intercomparison of atmospheric dynamical cores in general circulation models (GCMs). Test category 1 examines the advective transport of passive tracers by three‐dimensional prescribed wind velocity fields, on the sphere. These tests are applied to the Spectral Element (SE) dynamical core of the Community Atmosphere Model (CAM), the default for high‐resolution simulations in the Community Earth System Model (CESM). Test case results are compared with results from the CAM‐FV (Finite Volume) and MCore models where possible. This analysis serves both to evaluate the performance of CAM‐SE's spectral‐element tracer transport routines as well as to provide a baseline for comparison with other atmospheric dynamical cores and f or future improvements to CAM‐SE itself.